(untitled) (Medical Forum Monthly, 2024)
The death rate from asthma attacks is steadily creeping up. Asthma is a common chronic inflammatory disease of the airways characterized by reversible airflow obstruction, and bronchospasm. Symptoms include wheezing, coughing, chest tightness, and shortness of breath. The diagnosis is made clinically.1 These symptoms vary over time, and from individual to individual. More than 300 million people worldwide suffer from this disabling disease and this figure is projected to rise by nearly 50% every decade.2 The International Study of Asthma and Allergies in Childhood (ISAAC) study mentioned a prevalence of 8% in Pakistani paediatric population back in 2008.3 The current prevalence is estimated to be around 11%, though the figure has not been confirmed. The first sign of disease is a persistent cough. Symptoms may occur several times in a day or week in the effected. For some people the symptoms become worse during physical activity or at night. Failing to recognize triggers that lead to a tightened airway can easily be fatal. The major risk factors for developing asthma are:familial atopic background, urban residence, passive smoking and early weaning were important risk factors for childhood asthma,4 exposure to indoor allergens such as house dust mites in bedding, carpets, curtains, stuffed furniture; pollution, exposure to cats and dogs in the first two years of life, cockroaches; and outdoor allergens such as pollens, moulds; tobacco smoke and chemical irritants. Other minor risk factors includeprenatal exposure to active maternal smoking, exposure to second hand smoke after birth, respiratory infections in childhood, low birth weight, obesity, persistent allergic rhinitis, scented cosmetics, and medicines such as aspirin and beta-blockers. Asthma triggers include cold air, extreme emotional arousal and physical exercise. The most alarming factor; there is no cure for asthma, even though there are some very effective medicines which, when properly used, can largely control asthma attacks and allow people to lead a normal life.Correctly using anti-asthma medication and avoiding allergens is really the cornerstone in achieving control. Inhalers are the first line of treatment and are the safest way of delivering medicine to the lungs. Preventive measures include;reduction in level of exposure to common risk factors including smoking and environmental tobacco smoke, indoor air pollutants and keeping indoor humidity low, maintaining a healthy weight, controlling insects such as cockroaches, and not keeping pets inside the house. Every year the Global Initiative For Asthma holds aWorld Asthma Day. In 2015, it took place on Tuesday, May 5, 2015 and the theme was "You Can Control Your Asthma." GINA also continued to use the sub-theme, "It's Time to Control Asthma." Planning seminars for public awareness, and observing the World Asthma Day, could serve as important milestones in increasing awareness in the public and us doctors alike. It is time that we, the doctors of this country try to realize the gravity of this situation. If statistics are to be relied upon, nearly every 11th child in our country could be asthmatic, and we need to strive towards improving care and diagnosing asthma properly and in a timely fashion in our paediatric population.